2010
DOI: 10.3382/ps.2009-00382
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineralization in male commercial broilers and its relationship to gait score

Abstract: Broilers selected for increased body size and breast muscle have imposed stress on the skeletal system, resulting in poorer walking ability. Our objectives were to determine the relationship between bone mineralization and gait score in 4 crosses of commercial broilers and to ascertain if mineralization of the toe is correlated to the tibia. Three chickens per pen each with good (gait score of 0 or 1) or poorer (gait score of 3) walking ability were killed and weighed. The left humerus, the left middle toe, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Leterrier and Nys (1992) comparing tibial growth of slow and fast growing broilers showed that rate of growth was associated with lower mineral density and higher porosity of the tibial cortices (comparison at similar weights). On the other hand, the recent study of Talaty et al (2010) comparing four commercial broiler crosses shows that bone mineral density was similar between crosses. There is another report that shows that the bones of a fast-growing selected strain are more porous and less well mineralised than those of a slower-growing control strain (Williams et al, 2000).…”
Section: Musculoskeletal Disordersmentioning
confidence: 94%
“…Leterrier and Nys (1992) comparing tibial growth of slow and fast growing broilers showed that rate of growth was associated with lower mineral density and higher porosity of the tibial cortices (comparison at similar weights). On the other hand, the recent study of Talaty et al (2010) comparing four commercial broiler crosses shows that bone mineral density was similar between crosses. There is another report that shows that the bones of a fast-growing selected strain are more porous and less well mineralised than those of a slower-growing control strain (Williams et al, 2000).…”
Section: Musculoskeletal Disordersmentioning
confidence: 94%
“…The defects were also found in ostriches HOR-BAÑCZUK et al 2004). The problems with lower limb bones concern mainly males (CHARUTA et al 2012c;TALATY et al 2010).…”
mentioning
confidence: 99%
“…Bone breaking strength, bone ash concentration, and bone weight are positively correlated with BMD and BMC obtained by DXA in chickens (Fleming et al, 1994;Mazzuco and Hester, 2005;Kim et al, 2006Kim et al, , 2008. There is a strong correlation between BMD and BMC (r=0.81; p<0.01) in White Leghorns (Hester et al, 2004) as well in male broilers of commercial lines (Talaty et al, 2010). In addition, relatively larger bones present higher BMC correlation with total bone mineral content and are stronger and BMD and BMC values increase with broiler BW (Schreiweis et al, 2004).…”
Section: Edible Giblets and Bone Mineral Characteristics Of Two Slow-mentioning
confidence: 69%
“…BMD is a noninvasive method using dual-energy x-ray absorptiometry (DXA) that has also been employed to predict osteoporosis in humans (Bolotin, 2007;Koo, 2000). DXA could also be used to measure BMC in broilers and laying hens (Schreiweis et al, 2005;Shim et al, 2012;Talaty et al, 2010).…”
Section: Introductionmentioning
confidence: 99%